(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The problem of protecting spacecraft from cosmic dust has recently come to the fore. There is still no enough data on the complex effect of short-term high-energy, dynamic loading on materials, including polymer materials and multilayer polymer-metal composites. The use of dynamic alloying in the super-deep penetration (SDP) mode by high-speed flows of powder particles allows assessing the effect on the material under dynamic action. Previous studies on steel and aluminum samples have shown a significant effect of high-speed flows of powder particles on the structure and properties of materials. As a result of a study of samples made of aliphatic polyurethane with steel reinforcement elements, it was found that there are traces of the penetration of high-speed particles into both metal and polymer layers. However, the number of flow elements detected in the polymeric part is significantly less than the number of elements in the metal reinforcing part. Thus, it is possible to assume that or the polymer material is a more effective barrier to the high-speed flow compared to the metal, or the “self-healing” effect is observed.